Planning and Implementation of Building Maintenance Strategies - Cheong Peng Au-Yong; Shirley Jin Lin Chua (2024)
This book is an exploration of the intricate process of planning and implementing effective building maintenance strategies. In the realm of construction and property management, building maintenance plays a vital role in ensuring the longevity, functionality, and value of our built environment. The purpose of this book is to serve as a comprehensive guide, offering insights, knowledge, and practical tools for professionals and enthusiasts alike who are involved in building maintenance Whether you are a facility manager, maintenance technician, property owner, or aspiring expert in the field, this book aims to equip you with the necessary understanding and strategies to make informed decisions and optimize maintenance efforts.Throughout the pages of this book, we delve into the fundamental concepts and principles of building maintenance strategies, exploring the importance of proactive planning, effective execution, and continuous evaluation. We delve into topics such as building maintenance strategies, characteristics of planned maintenance, participative mechanisms in planned maintenance and the maintenance of building facilities and services all of which contribute to the development of robust maintenance strategies.It is our hope that the knowledge imparted within these pages will empower you to enhance the efficiency, functionality, and lifespan of the buildings under your care.